Un’analisi della condizione abitativa degli stranieri a Roma e Milano: micro-segregazione e periferizzazione - Costarelli, Igor; Mugnano, Silvia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
In many North European cities, ethnic residential segregation dates back to mid- seventies. In these contexts, the growing spatial concentration of immigrants has been perceived as a threat to social cohesion, fuelling urban de-segregation and territorial dispersal policies. Within this framework, ethnic segregation is rather an emerging issue in many Southern European countries, assuming very different connotations and nuances. After discussing the features of this phenomenon, this paper focuses on residential patterns and housing conditions of immigrants in Italy. The paper proposes a spatial analysis of the distribution of immigrant populations in Milan and Rome in the new millennium by using register data. This paper discusses some of the possible implications that stem from micro-segregation and peripheralisation dynamics, questioning the inclusiveness of cities.